2000
DOI: 10.2527/2000.78112842x
|View full text |Cite
|
Sign up to set email alerts
|

Rigor temperature and meat quality characteristics of lamb longissimus muscle.

Abstract: The present experiment was conducted to determine the effect of muscle temperature during the prerigor and early postrigor period on meat tenderness, postmortem proteolysis, calpain system activity, water-holding capacity, and color. Lamb longissimus muscle (n = 14) from the right and left carcass sides was excised immediately after dressing, divided into an anterior and posterior sample, vacuum-packaged, and stored overnight at 5 to 35 degrees C. Further storage, up to 14 d postmortem, was at 2 degrees C. Ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 19 publications
7
62
0
7
Order By: Relevance
“…It is also important to note that the improvement in tenderness during aging was not negatively affected when the stretched muscles were kept at 37 C before rigor. Numerous studies have reported limited aging potential of muscles that were exposed to high pre-rigor temperature (Lee and Ashmore 1985;Hertzman et al 1993;Dransfield 1994;Devine et al 1999Devine et al , 2002Geesink et al 2000;Hwang and Thompson 2001;Thomson et al 2008;Kim et al 2010Kim et al , 2012Rosenvold and Wiklund 2011). Further, some studies have reported a transient effect of stretching muscles -improved tenderness during the early post-mortem period, but no further benefit with aging (Taylor et al 2012;Toohey et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to note that the improvement in tenderness during aging was not negatively affected when the stretched muscles were kept at 37 C before rigor. Numerous studies have reported limited aging potential of muscles that were exposed to high pre-rigor temperature (Lee and Ashmore 1985;Hertzman et al 1993;Dransfield 1994;Devine et al 1999Devine et al , 2002Geesink et al 2000;Hwang and Thompson 2001;Thomson et al 2008;Kim et al 2010Kim et al , 2012Rosenvold and Wiklund 2011). Further, some studies have reported a transient effect of stretching muscles -improved tenderness during the early post-mortem period, but no further benefit with aging (Taylor et al 2012;Toohey et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of high pre-rigor temperature on meat quality attributes such as tenderness, water-holding capacity and colour has been studied in excised muscle, and almost exclusively on the longissimus muscle. It has been generally agreed that keeping excised pre-rigor longissimus muscles at a high temperature (normally !35 C) results in lower tenderness (often called heat-induced toughening), more fluid loss from meat and paler colour (Jaime et al 1992;Hertzman et al 1993;Devine et al 1999Devine et al , 2002Geesink et al 2000;Rosenvold et al 2008). Warner et al (2014b) and others have shown the detrimental effects of high rigor temperature on the tenderness, water-holding capacity and colour of beef longissimus and GM muscles from a carcass (rather than excised).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that both pH and temperature can have dramatic effects on μ-calpain autolysis and activity (Koohmaraie, 1992;Camou et al, 2007), while Ca 2+ concentrations (needed for calpain activation) within postmortem muscle are greater at elevated temperatures (Goll et al, 2003). Additionally, calpastatin activity has been shown to decrease at elevated temperatures (Geesink et al, 2000;Pomponio and Ertbjerg, 2012), while its inhibition of μ-calpain appears to not be influenced by pH (Geesink and Koohmaraie, 1999;Maddock et al, 2005). Therefore, alterations in muscle temperature and resulting pH in this study may have the potential to influence μ-calpain activity and meat aging; however, limited research has been performed evaluating μ-calpain activity and subsequent postmortem proteolysis under differing early postmortem conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The pH of the homogenate was measured at around 20 °C using the same pH meter as used for measuring the pH of the carcasses. The surface colour of the muscles was recorded in samples (Geesink et al, 2000) using a ColorTec-PCM/PSM Color Meter with a 12 mm aperture (Model U59730-30, Cole-Parmer International, USA). Colour was expressed in terms of CIE values for lightness (L*), redness (a*), and yellowness (b*).…”
Section: Methodsmentioning
confidence: 99%